1990
DOI: 10.21273/hortsci.25.9.1163d
|View full text |Cite
|
Sign up to set email alerts
|

Expanded Shale as a Potting Medium Component for Bedding Plants

Abstract: Expanded shale and peat moss were mixed in 5 ratios and evaluated as potting media for Petunia and Impatiens. Two grades of shale (coarse and fine) were used. Bulk density increased linearly with increasing shale whereas total pore space and container capacity increased linearly with increasing peat. Air space of peat-fine shale was consistently lower than that of peat-coarse shale when the peat/shale ratio was the same. Container capacity of peat-fine shale was consistently higher than that of peat-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Ferguson (2005) describes Expanded Shale as porous and stable aggregates, the properties which allow expanded shale to be a favorite component of plant potting media. Nash et al (1990) concluded that the growth of plants was enhanced in a medium amended with Expanded Shale and peat moss. Although the benefits of Expanded Shale on plant growth were well documented, there is lack of data in current literature on the effect of Expanded Shale on the hydraulic conductivity of fine grained soils.…”
Section: Introduction Expanded Shale As Soil Amendmentmentioning
confidence: 99%
“…Ferguson (2005) describes Expanded Shale as porous and stable aggregates, the properties which allow expanded shale to be a favorite component of plant potting media. Nash et al (1990) concluded that the growth of plants was enhanced in a medium amended with Expanded Shale and peat moss. Although the benefits of Expanded Shale on plant growth were well documented, there is lack of data in current literature on the effect of Expanded Shale on the hydraulic conductivity of fine grained soils.…”
Section: Introduction Expanded Shale As Soil Amendmentmentioning
confidence: 99%
“…In the 50-PB/50-BS blend of organic materials and the traditional 75-PB/25-PM blend, maple growth was unaffected by the addition of 15% and 30% expanded shale, but was decreased by the addition of 60% expanded shale, probably due to a reduction in the quantity of plant available nutrients and water. Other researchers have observed decreased plant growth in organic-based growing media as the percentage of expanded slate or shale was increased (Carlile and Bedford, 1988;Nash et al, 1990;Rowe et al, 2006).…”
Section: Expanded Shale Content (%)mentioning
confidence: 93%